Penguatan Pembekalan Kemampuan Pemrograman Dasar bagi Pelajar Sekolah Menengah Umum - Susana Limanto; Liliana Liliana; Daniel Soesanto; Maya Hilda Louk; Bambang Prijambodo (Warta LPM, 2023)
Basic programming training that teaches problem-solving logic has developed at all ages, from kindergarten, elementary school to higher education age. This happens because at this time, the concept of computing or informatics thinking has been considered to be a basic requirement in everyday life. Various forms of learning the concept of informatics thinking, are designed according to the user's age group so that users can enjoy it.  In the community service activities carried out this time, the target of basic programming training is Public High School students, which are open to all schools in Indonesia. This activity was implemented during the Covid-19 pandemic, so this activity was carried out online in the form of a bootcamp through the Zoom meeting application regularly in one month, which was led as a team by a lecturer and several teaching assistants. This training does not stop at delivering material and demonstrations from lecturers but also training assistance conducted by teaching assistants. The material in this training uses the Python programming language. Python was chosen to be used in the training, because currently Python is a programming language that is widely used for simple to complex programming such as data mining and machine learning. Participants can access training materials through the Learning Management System created by Universitas Surabaya to support the dissemination of knowledge to the wider community through the Ubaya Global Academy) platform. Based on the evaluation of the activities carried out before and after the activity was carried out, this activity is considered to provide benefits and can be carried out regularly every year and has follow-up classes.